PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. GRAHA PENA JAKARTA SELATAN - Faiz Nurhalim Majid; Imbron (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of leadership style and compensation on employee performance at PT. Graha Pena South Jakarta. This research uses a descriptive method with a quantitative approach. The sample collection technique used saturated sampling and the sample obtained in this study was 60 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this research show that: (1) There is a partial influence obtained by Tcount 1.242 < Ttable 2.001. Thus, Ha1 is rejected and H01 is accepted, meaning that there is no influence on leadership style on employee performance at PT. Graha Pena, South Jakarta. (2) There is a partial influence obtained by Tcount 2.922 > Ttable 2.001. Thus, Ha2 is accepted and H02 is rejected, meaning that there is an influence on compensation on employee performance at PT. Graha Pena, South Jakarta. (3) There is a simultaneous influence obtained by Fcount 23.116 > Ftable 3.160. Thus, Ha3 is accepted and H03 is rejected, meaning that there is an influence on leadership style and compensation together on employee performance at PT. Graha Pena South Jakarta.